From Real Class to a Global Network Education In High Academic Achievement International Doctoral Groups [HAAIDG] - Martines Peres, Vicent (IJERI: International Journal of Educational Research and Innovation, 2018)
Research, develop and implement strategies and methodologies aimed at the establishment of HIGH ACADEMIC ACHIEVEMENT INTERNATIONAL DOCTORAL GROUPS [HAAIDG, in Spanish acronym: GARAID]. In current Doctorate studies, collaboration, coordination and cooperation for research and innovation in official studies leading to the PhD degree developed at the University of Alicante and, in general, at the University of Alicante are still more necessary than before. Other universities, taking into account the frame of reference of the European Higher Education Area. The HAAIDG have been applied first in the "Doctoral Program in Intercultural and Historical Relations in Medieval Mediterranean Europe" -in ISIC-IVITRA and Prometeo de Excelencia PrometeoII/2014/018, University of Alicante-. Many of the needs and challenges to which an attempt is made to respond through HAAIDG are transversal and common to doctoral studies in general: distance learning, teaching by often remote tutorials, internationalization, stays abroad, highly specialized lines and research teams, need to generate knowledge with theses, need for transfer (publications, participation in scientific meetings, both previously and subsequently to the thesis and derived from it).